1983
DOI: 10.1099/0022-1317-64-7-1475
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Herpes Simplex Virus Replication by Cobra  -Neurotoxoid

Abstract: SUMMARYA peptide, prepared by gentle oxidative detoxification of a methionine-free cobra c~-neurotoxin, was evaluated for antiviral activities in vivo and in vitro. When added to BHK cells before infection the peptide reduced herpes simplex virus type 1 (HSV-1)-induced TCDs0 in a dose-and time-dependent manner. The antiviral effect was also expressed on initiation of cell treatment 1 h after infection if the peptide was left in contact with cells. Single, intracerebral doses of the toxoid in suckling mice sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…After subcutaneous injection of 0.1 mL cobra venom preparation daily (trade name Bioven) for 1 month, the viral load of the patient decreased from 1,580,000 copies/mL to 3274 copies/mL and the CD4 count increased from 52/mm 3 to 324/mm 3 [ 11 ]. The peptide derived from oxidative detoxification of α-neurotoxin could reduce herpes virus replication in infected brain tissues and increase survival time by 50% in mice [ 12 ]. In addition, cobrotoxin has a certain similarity to ACE2 according to sequence alignment results.…”
Section: Broad-spectrum Antiviral Activities Of Cobra Venom and α-Neumentioning
confidence: 99%
“…After subcutaneous injection of 0.1 mL cobra venom preparation daily (trade name Bioven) for 1 month, the viral load of the patient decreased from 1,580,000 copies/mL to 3274 copies/mL and the CD4 count increased from 52/mm 3 to 324/mm 3 [ 11 ]. The peptide derived from oxidative detoxification of α-neurotoxin could reduce herpes virus replication in infected brain tissues and increase survival time by 50% in mice [ 12 ]. In addition, cobrotoxin has a certain similarity to ACE2 according to sequence alignment results.…”
Section: Broad-spectrum Antiviral Activities Of Cobra Venom and α-Neumentioning
confidence: 99%
“…For example, the toxic effects of cardiac glycosides on animals and apicomplexan parasites likely stem from interference with different types of ATPases (Gowler, Leon, Hunter, & de Roode, 2015;Petschenka et al, 2013;Spillman & Kirk, 2015). Importantly, studies have shown inhibition of herpes simplex virus replication by a neurotoxin isolated from cobra venom (Yourist, Haines, & Miller, 1983), demonstrating that chemicals that are traditionally known for their toxic effects on vertebrate neurons can also inhibit the growth of neuron-free viruses.…”
Section: Discussionmentioning
confidence: 99%